A pesca como proposta temática da educação ambiental popular no 6° ano do ensino fundamental no norte do Tocantins - Nascimento , Mateus Filho Vieira do (2024)
This work aims to understand how fishing, as a bodily practice, can contribute to classes in the final years of Elementary School II, focusing on Environmental Education (EA). The research took place at Escola Estadual Girassol de Tempo Integral XV de Novembro, in Tocantinópolis – TO, with children in the 6th year. The study is anchored in Popular Environmental Education, as it presents a problematizing perspective of reality based on the political dimension of education. The work is justified by the relevance of Environmental Education in schools, especially in its transforming and sociocultural character, elements of a formative nature (BRASIL, 2017). In addition, visibility is given to the context of artisanal fishing on the Tocantins River, by taking place in a school with a riverside setting, through Action-Research with a Qualitative approach. Assuming the following question “How do popular knowledge arising from children and their experience with fishing help in the elaboration of a proposal involving Environmental Education at Escola Estadual Girassol de Tempo Integral XV de Novembro, in Tocantinópolis-TO?”. The results show that the research participants were able to bring the elements present in the fishing communities, highlighting the relevance of popular knowledge for the community itself and its manifestation as knowledge to be addressed in the school environment. In addition, through the pedagogical activities of the educational project, it was understood that the research participants demonstrated critical thinking in the face of socio-environmental causes. Furthermore, by establishing a close relationship between children and the environment, we bring to light the need for a dialogue between body and nature, essential elements for discussion in the school environment and potentializers of meaningful teaching, fostering the relevance of research that addresses the environmental context related to the social dimension.